Penerapan Strategi Cooperative Learning Pada Mata Pelajaran SKI Kelas VII MTs Darul Aitami Aceh Selatan - Tazkirah Khaira; Zulfatmi Zulfatmi (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2022)
Learning strategy can be interpreted as a plan that contains a series of activities designed to achieve certain educational goals. Cooperative learning is learning that is carried out together or in groups between students and other students, who help each other in solving a problem on the material that has been given by the teacher in order to achieve completeness in achieving the lesson. Learning Islamic Cultural History (SKI) is a conscious effort made by the teacher to provide knowledge to students about important events that occurred in Islamic civilization and its figures with the aim of motivating students towards noble behavior changes. This study aims to describe the implementation of cooperative learning in SKI class VII MTs Darul Aitami Aceh Selatan. This study used a qualitative approach with descriptive analysis of the data that the author obtained in the field. Data collection was done by interview and observation. The author conducted interviews with SKI subject teachers and the author made continuous observations of class VII. And the results of the study show that the application of cooperative learning carried out by SKI subject teachers at MTs Darul Aitami is fairly